Formation of the Concept of Development and Modernisation of Competitive Hotel and Restaurant Establishments in Conditions of Global Threats - Олена Завадинська; Валентина Русавська (Ресторанний і готельний консалтинг: Інновації, 2025)
Topicality. The relevance of the selected study grounds on the fact that recent global events such as the armed aggression of the russian federation against Ukraine in 2022 and the COVID-19 pandemic have made significant changes to the usual rhythm of life of everyone, regardless of the country of residence. These circumstances form the basis for studying and analysing the development of hotel and restaurant establishments in the face of global threats with the further aim of creating a comprehensive system of sustainable development, which, in turn, will become an important direction in ensuring the national economy’s development. The aim and methods. The aim of the study is to analyse the current situation in the formation of the concept of development and modernisation of competitive hotel and restaurant establishments in the face of global threats. The research methods are based on the analysis of specialised literature on the research problem, covering the basics of the Concept of Development, generalisation and synthesis of the studied material for further work on the problem, data collection and statistical groupings, mathematical calculations, construction of graphic materials, application of economic research methods, systematisation of the obtained material, implementation of research and experimental work. Results. The article studies the activities of the hotel and restaurant industry in constrained conditions based on domestic and foreign experience; describes the concepts of development of the service sector from classical interpretations to modern challenges; describes the organisation of the hotel and restaurant business based on the fundamental principles of the military sphere, and forms a concept of development and modernisation of competitive hotel and restaurant establishments in the context of global threats. Conclusions and discussion. The scientific novelty of the article grounds on the development of scientific and practical recommendations aimed at ensuring the sustainable development of hotel and restaurant establishments in the context of global threats. The practical significance lies in the fact that the scientific and practical provisions of this research can be implemented in the hospitality industry in order to increase resilience in the face of global threats.